The Influence of Managerial Myopia on Strategic Differentiation: A Decision-Making Perspective - Tianjiao Zhang; Qingqing He; Yanan Gao (Decision Making: Applications in Management and Engineering, 2025)
In highly complex and evolving business environments, the methodological soundness of corporate strategic decision-making plays a pivotal role in shaping both organizational risk resilience and competitive positioning. This research integrates Upper Echelons Theory with Strategic Balance Theory to construct a decision science framework that examines the interrelationship among managerial language, cognitive orientation, and strategic behaviour. Employing text mining techniques, the study quantifies executive myopic tendencies within Management Discussion & Analysis (MD&A) disclosures and systematically assesses their influence on corporate strategic differentiation. The analysis utilises panel data from A-share listed companies on the Shanghai and Shenzhen stock exchanges over the period 2014–2022. Based on the outcomes of the Hausman test, a fixed-effects model is applied as the principal estimation method. To enhance methodological robustness, Propensity Score Matching (PSM) is implemented to address potential sample selection bias, while Two-Stage Least Squares (2SLS) estimation is used to correct for endogeneity concerns. Empirical results indicate that managerial myopia exerts a significantly negative impact on strategic differentiation, with findings remaining consistent after controlling for firm age, size, profitability, and other relevant covariates. Mediation analysis reveals that risk-taking propensity serves as a complete mediator, whereas moderation tests indicate that the effect is intensified in state-owned enterprises and firms with limited analyst coverage. These findings carry important implications for strategic decision-making: organisations are encouraged to adopt mechanisms that mitigate cognitive biases through decision-support systems and enhanced executive performance metrics. Policymakers may consider implementing stricter disclosure regulations, promoting analyst engagement for under-covered firms, and facilitating state-owned enterprise reform via mixed-ownership strategies to foster system-wide strategic innovation.